MEASUREMENT AND ACCOUNTING DISCLOSURE OF SOCIAL RESPONSIBILITY COSTS - Dr. Fatemeh darogheh hazrati; Waseem Saleh Khalaf; Oday Fathi Jarullah; Sulaiman Hamad Atiyah; Sarmad Hussein Atiyah (Scholar Express Journals, 2022)
The issue of accounting for social responsibility for business organizations is still one of the issues that raise controversy among researchers, regarding defining its concept, nature, measurement and disclosure to all the beneficiary parties. The social performance of the establishments. Contemporary accounting disclosure seeks to meet the information needs of the owners of the economic unit and all the beneficiaries of the financial statements, whether those categories are internal or external, and during this research, the concepts of measurement and accounting disclosure of social responsibility were clarified, as the concept of accounting measurement included the concept of preserving capital that should be used as a basis for measuring Income and this entails determining the changes in the financial position that represent the parts of the enterprise’s income. The concepts of accounting measurement have been defined on the basis that income is not produced until after preserving the cash capital, While disclosure is generally defined as relating to information that appears both in the basic financial statements and additional means of communication, which in turn includes guidance notes, a statement of subsequent events, and management's analysis of operations that may occur in the next year . The methods of accounting measurement have been discussed, where there are two methods of measurement, the first method is to measure the costs of preventing the occurrence of damages and the second method is the costs of restoring the situation to what it was (correction costs), as well as mentioning the most important methods of accounting disclosure, and the problems that face accounting measurement operations
Keywords: Social responsibility accounting; social responsibility accounting measurement; social responsibility accounting disclosure